Memahami QS Al A’raf Ayat 56 mengenai Perampasan Lahan: Telaah Penafsiran Kontekstual menurut Pendekatan Abdullah Saeed - Firdaus Dahlan; Achmad Abubakar; Halimah Basri; Ria Renita Abbas (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
One of the human practices that cause damage to nature is land tenure or land grabbing which is then exploited in such a way for economic gain. This is very different from the text of the Quran which encourages humans to maintain environmental balance. In Q.S. A'raf verse 56, when viewed from the concept of Abdullah Saeed's Hierarchy of Values, the verse falls into Instructional Value, the impact of which will have two meanings. The universal meaning and the particular meaning. The purpose of this study is to find out the universal and particular meanings and relate them to the phenomenon of land grabbing. Thus, the universal meaning of verse 56 of QS Al A'raf is not to interfere with common rights that can cause harm to anyone. The particular value of the verse is the prohibition of land tenure because it is closer to indications of land grabbing that reduce access and movement of surrounding communities who may have felt marginalized and have no power to fight back or even just protest.